2006
DOI: 10.1007/s10495-006-0571-1
|View full text |Cite
|
Sign up to set email alerts
|

Different levels of p53 induced either apoptosis or cell cycle arrest in a doxycycline-regulated hepatocellular carcinoma cell line in vitro

Abstract: Induction of p53 gene expression in cancer cells can lead to both cell cycle arrest and apoptosis. To clarify whether the level of p53 expression determines the apoptotic response of hepatocellular carcinoma (HCC) cells, we assessed the effect of various levels of expression of p53 gene on a p53-deficient HCC cell line, Hep3B, utilizing a doxycycline (Dox)-regulated inducible p53 expression system. Our results showed that apoptosis was induced in HCC cells with high levels of p53 expression. However, lower lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
43
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 21 publications
6
43
0
1
Order By: Relevance
“…It is well known that p53 mediates cell cycle arrest and apoptosis in tumour cells (Lai et al, 2007). The results from our study also showed that p53 mediates cell cycle arrest and apoptosis of macrophages upon L. interrogans infection.…”
Section: Discussionsupporting
confidence: 83%
“…It is well known that p53 mediates cell cycle arrest and apoptosis in tumour cells (Lai et al, 2007). The results from our study also showed that p53 mediates cell cycle arrest and apoptosis of macrophages upon L. interrogans infection.…”
Section: Discussionsupporting
confidence: 83%
“…Some researches have reported that the antitumor effect of doxycycline is associated with different levels of p53 in hepatocellular carcinoma [18]. Another study demonstrates that doxycycline can induce apoptosis in human pancreatic and colon cancer cells through caspase-dependent way [19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Fas proteins, which are increased by DOX, interact with FasL on T cells and result in Fas-mediated death of T cells. Furthermore, DOX changes the expression pattern of a multitude of genes involved in cell cycle regulation (p53, CDK10, and Gadd45) and apoptosis and cell damage (Fas and Bax) [13][14][15][16] . The p53 tumor suppressor gene, which is an essential transcription factor involved in cell cycle checkpoints, upregulates cell cycle modulators such as the cyclin-dependent kinase inhibitor p21 and GADD45, which is rapidly induced by genotoxic reagents [17] .…”
Section: Introductionmentioning
confidence: 99%
“…The molecular mechanisms governing the relationship between DNA damage, cell cycle arrest at G 2 /M, and inhibition of cell division remain poorly defined [18] . High levels of induction of p53 may result in apoptosis, while low expression of p53 may cause cell cycle arrest without cell death [14] . The GADD45 family is rapidly induced in response to pathological stimuli such as hypoxia, irradiation, and genotoxic drugs.…”
Section: Introductionmentioning
confidence: 99%